Recchia sessiliflora (Surianaceae Arn.), a new species from the Balsas Depression in the state of Guerrero, Mexico - González-Murillo, Andrés; Cruz Durán, Ramiro; Jiménez Ramírez, Jaime (Instituto de Ecología, A.C., 2014)
A new species from the Balsas Depression in the state of Guerrero, Mexico, Recchia sessiliflora (Surianaceae Arn.), is described and illustrated. This new species is similar to Recchia connaroides (Loes. & Soler) Standl., differing from the latter in having smaller, elliptic to suborbicular leaflets which increase in size towards the apex of the leaf, a rachis which is clearly winged, a spicate inflorescence and flowers with oblanceolate and irregularly emarginate petals. This species is currently only known from its type locality in tropical dry forest. A comparative table with distinctive characteristics of similar species, a distribution map, and a dichotomous key to distinguish among the known species for the genus Recchia Moc. & Sessé ex DC. are also provided.